Kenyatta University/UNESCO : international seminar report, curriculum reorientation in rural development implications for home economics - Susan Van der Vynckt edited by (Paris : Division of Education for the quality of life, 1991)
Kenyatta University, the craddle of music scholarship and performance in Kenya presents its music.
Copyright: Kenyatta University.
Camera, Gordon Otieno ; sound, James Wasonga ; editors, Minnie Ponda, Julius Ungadi.
Josephine Muigai.
Title in Swahili.
Keywords: Education research